Biochemical and morphological effects of fumonisin B-1 on primary cultures of rat cerebrum - Kwon, OS; Slikker, W; Davies, DL (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Chronic dietary consumption of the mycotoxin fumonisin B-1 (FB1) is associated with leukoencephalomalacia and neuronal degeneration, but identification of the cellular mechanisms underlying this neurotoxicity is difficult due to concurrent adverse systemic changes. For this reason, the present investigation used an in vitro approach to assess the short-term consequences of direct FB1 (0.5-75 mu M) exposure on astrocytes and oligodendrocytes in primary cultures of rat cerebrum. Beginning at 5 days in vitro, the cultures were exposed to FB1 at five concentrations (0.5-75 mu M), and the cultures were evaluated at 10 and 15 days in vitro. The levels of the sphingolipid-associated constituents sphingosine and sphinganine were determined with a high-performance liquid chromatography. Relative to untreated cultures, exposure to FB1 diminished the levels of sphingosine at 15 days in vitro, whereas FB1-exposed cultures showed significantly increased sphinganine levels and sphinganine/sphingosine ratios. In addition to these changes in sphingolipid constituents, FB1-exposed (0.5-75 mu M) cultures exhibited a two-fold increase in the number of process-bearing cells by 15 days in vitro. Also, the activity of 2',3'-cyclic nucleotide 3'-phosphohydrolase, an enzyme associated with myelin and oligodendrocytes, was increased in FB1-treated cultures. This study suggests that shortterm exposure to FB1 may modify the proliferation or differentiation of glial cells. (C) 2000 Elsevier Science Inc. All rights reserved.